THE USE OF CRITICAL INCIDENT IN TEACHING WRITING SKILL TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI MARGA TUNGGAL - Episiasi Episiasi (Universitas Lancang Kuning, 2017)
The problem of this research was “Is it significantly effective to teach writing by using Critical Incident to the eighth grade students of SMP Negeri Marga Tunggal in Academic Year 2016/2017?” Therefore, the objective of this research was to find out whether or not it was significantly effective to teach writing by using Critical Incident. In this research, the researcher proposed two hypotheses. That is, null hypothesis (Ho) and alternative hypothesis (Ha). The method applied was pre-experimental. The number of the sample was 34 students. The data were collected by using writing test. The data obtained analyzed through four techniques: 1) Individual Score, 2) Comparison to Minimum Mastery Criteria, 3) Normality Testing and 4) Paired t-test calculation. The results of this research: (1) Students’ mean score in the pre-test was 64.26, (2) Student’ mean score of post-test was 71.57 and (3) the result of paired t-test was 5.66, which was higher than 1.697 value of the ttable with 95% significant level for one tailed-test. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It means that it was significantly effective to teach writing by using Critical Incident to the eighth grade students of SMP Negeri Marga Tunggal in academic year 2016/2017.